Proestrus Differentially Regulates Expression of Ion Channel and Calcium Homeostasis Genes in GnRH Neurons of Mice - Vastagh, Csaba; Solymosi, Norbert; Farkas, Imre; Liposits, Zsolt (Frontiers in Molecular Neuroscience, 2019)
In proestrus, the changing gonadal hormone milieu alters the physiological properties of GnRH neurons and contributes to the development of the GnRH surge. We hypothesized that proestrus also influences the expression of different ion channel genes in mouse GnRH neurons. Therefore, we performed gene expression profiling of GnRH neurons collected from intact, proestrous and metestrous GnRH-GFP transgenic mice, respectively. Proestrus changed the expression of 37 ion channel and 8 calcium homeostasis-regulating genes. Voltage-gated sodium channels responded with upregulation of three alpha subunits (Scn2a1, Scn3a and Scn9a). Within the voltage-gated potassium channel class, Kcna1, Kcnd3, Kcnh3 and Kcnq2 were upregulated, while others (Kcna4, Kcnc3, Kcnd2 and Kcng1) underwent downregulation. Proestrus also had impact on inwardly rectifying potassium channel subunits manifested in enhanced expression of Kcnj9 and Kcnj10 genes, whereas Kcnj1, Kcnj11 and Kcnj12 subunit genes were downregulated. The two-pore domain potassium channels also showed differential expression with upregulation of Kcnk1 and reduced expression of three subunit genes (Kcnk7, Kcnk12 and Kcnk16). Changes in expression of chloride channels involved both the voltage-gated (Clcn3 and Clcn6) and the intracellular (Clic1) subtypes. Regarding the pore-forming alpha-1 subunits of voltage-gated calcium channels, two (Cacna1b and Cacna1h) were upregulated, while Cacna1g showed downregulation. The ancillary subunits were also differentially regulated (Cacna2d1, Cacna2d2, Cacnb1, Cacnb3, Cacnb4, Cacng5, Cacng6 and Cacng8). In addition, ryanodine receptor 1 (Ryr1) gene was downregulated, while a transient receptor potential cation channel (Trpm3) gene showed enhanced expression. Genes encoding proteins regulating the intracellular calcium homeostasis were also influenced (Calb1, Hpca, Hpcal1, Hpcal4, Cabp7, Cab 39l and Cib2). The differential expression of genes coding for ion channel proteins in GnRH neurons at late proestrus indicates that the altering hormone milieu contributes to remodeling of different kinds of ion channels of GnRH neurons, which might be a prerequisite of enhanced cellular activity of GnRH neurons and the subsequent surge release of the neurohormone.